A Case of Brain Abscess Caused by Medication-Related Osteonecrosis of the Jaw. (2nd February 2016) - Yamagata, Kenji; Nagai, Hiroki; Baba, Osamu; Uchida, Fumihiko; Kanno, Naomi; Hasegawa, Shogo; Yanagawa, Toru; Bukawa, Hiroki
Abstract : Reports of brain abscesses caused by medication-related osteonecrosis of the jaw (MRONJ) are very rare. We here present the case of a 76-year-old man with terminal-stage prostatic carcinoma and a brain abscess caused by MRONJ at the maxilla. The patient had been treated with zoledronic acid and denosumab for bone metastasis. For the brain abscess, an antibiotic regimen based on ceftriaxone and metronidazole and a sequestrectomy contributed to a successful outcome. In the case of maxillary MRONJ extending to the maxillary sinus, active resection of the infected bone should be considered to prevent the spread of the infection beyond the maxillary sinus, into the ethmoid sinus, and into the brain.